The range of ice thrusts and ice piles as reflected by ice scars on trees growing on the shores of coastal lagoons: The case of the Szczecin Lagoon - Girjatowicz, Józef Piotr; Świątek, Małgorzata; Łabuz, Tomasz Arkadiusz (Quaestiones Geographicae, 2024)
We studied the phenomena associated with the thrusting of ice onto the shore of the Szczecin Lagoon based on the occurrence of tree ice scars. The measurements concerned mostly the maximum height, length and width of ice scars on trees, and the distance of these trees from the shore in the period 2017–2022. It was observed that sheets of ice advanced up to 64 m inland, and piled to form hummocks reaching up to 4.3 m above the water level. These maximum values occurred mostly on eastern shores, which is where the highest numbers of damaged and broken trees were observed. This should be associated with the strongest and most frequently occurring wind blowing from the western direction in the winter-spring period. To the contrary, the lowest number of damaged trees were observed on the western shore. This is due not only to the lower frequency of wind blowing from the east, and the associated cooling (Ta < 0°C) and ice cover stabilization, but also due to the presence of extensive reed belts. Our results enable an indirect insight into the ice phenomena dynamics, especially in areas lacking systematic ice observations. Similar conclusions may be extended for all the sheltered basins as lakes or lagoons.